Effect of using polyimide capillaries during thermal experiments on the particle size distribution of supported Pt nanoparticles. (1st October 2015) - Gámez‐Mendoza, Liliana; Resto, Oscar; Martínez‐Iñesta, María
<x xml:space="preserve">Abstract</x> Kapton HN‐type polyimide capillaries are commonly used as sample holders for transmission X‐ray experiments at temperatures below 673 K because of their thermal stability, high X‐ray transmittance and low cost. Using high‐angle annular dark field scanning high‐resolution transmission electron microscopy and thermogravimetric analysis, this work shows that using polyimide capillaries leads to the overgrowth of supported Pt nanoparticles during reduction at temperatures below the glass transition temperature (Tg = 658 K) owing to an outgassing of water from the polyimide. Quartz capillaries were also studied and this overgrowth was not observed.